FAKTOR-FAKTOR YANG MEMPENGARUHI RESPON PETANI TERHADAP TEKNOLOGI BUDIDAYA BAWANG MERAH RAMAH LINGKUNGAN DI KABUPATEN TEGAL - Tri Cahyo Mardiyanto (AGRITEXTS: Journal of Agricultural Extension, 2018)
Environmentally friendly onion cultivation technology in the onion development area in Central Java is one of the innovations to produce safe products and good quality seeds so that it will have a high competitiveness in the face of free markets such as the ASEAN Economic Community (MEA). However, this innovation to be implemented by all shallot farmers should be disseminated with the aim of accelerating  the  transfer  of  technological  innovation  to  users  (farmers,  extension officer,  and  rural  communities).  The  purpose  of  this  research  is:  (a)  to  know  the farmer's response about environmentally friendly onion cultivation technology and (b) to know determinant the factors of the farmer's response to the cultivation of environmentally friendly onion cultivation technology. Bottom of Form This research was conducted in 2016, in Tegal district, Central Java province with a sample of onion farmers. The analytic description method has been used in this research as the basic method, while the sampling method is purposive sampling on 40 onion farmers from 4 (four)  sub  districts  of  Kramat,  Dukuh  Turi,  Bojong,  and  Margasari.  Several  data analyzes in this study include: proportion test for hypothesis 1 and multiple linear regression analysis for hypothesis 2. In this study the final results used proportional analysis proved that many onion farmers (> 50%) in Tegal district have good response about the activities of environmentally friendly onion cultivation technology. Multiple linear regression analysis showed that farming time and farmer age significantly influenced farmer's response about environmentally friendly green onion cultivation technology, while education level significantly did not significantly    (α = 0,05).